Warm temperature acclimation impacts metabolism of paralytic shellfish toxins from Alexandrium minutum in commercial oysters. (29th May 2015) - Farrell, Hazel; Seebacher, Frank; O'Connor, Wayne; Zammit, Anthony; Harwood, D. Tim; Murray, Shauna
Abstract Species of Alexandrium produce potent neurotoxins termed paralytic shellfish toxins and are expanding their ranges worldwide, concurrent with increases in sea surface temperature. The metabolism of molluscs is temperature dependent, and increases in ocean temperature may influence both the abundance and distribution of Alexandrium and the dynamics of toxin uptake and depuration in shellfish. Here, we conducted a large‐scale study of the effect of temperature on the uptake and depuration of paralytic shellfish toxins in three commercial oysters (Saccostrea glomerata and diploid and triploid Crassostrea gigas, n = 252 per species/ploidy level). Oysters were acclimated to two constant temperatures, reflecting current and predicted climate scenarios (22 and 27 °C), and fed a diet including the paralytic shellfish toxin‐producing species Alexandrium minutum. While the oysters fed on A. minutum in similar quantities, concentrations of the toxin analogue GTX1, 4 were significantly lower in warm‐acclimated S. glomerata and diploid C. gigas after 12 days. Following exposure to A. minutum, toxicity of triploid C. gigas was not affected by temperature. Generally, detoxification rates were reduced in warm‐acclimated oysters. The routine metabolism of the oysters was not affected by the toxins, but a significant effect was found at a cellular level in diploid C. gigas. The increasing incidences of Alexandrium blooms worldwide are a challenge for shellfish food safety regulation. Our findings indicate that rising ocean temperatures may reduce paralytic shellfish toxin accumulation in two of the three oyster types; however, they may persist for longer periods in oyster tissue.